2020
DOI: 10.3390/antibiotics9020083
|View full text |Cite
|
Sign up to set email alerts
|

A Challenging View: Antibiotics Play a Role in the Regulation of the Energetic Metabolism of the Producing Bacteria

Marie-Joelle Virolle

Abstract: Antibiotics are often considered as weapons conferring a competitive advantage to their producers in their ecological niche. However, since these molecules are produced in specific environmental conditions, notably phosphate limitation that triggers a specific metabolic state, they are likely to play important roles in the physiology of the producing bacteria that have been overlooked. Our recent experimental data as well as careful analysis of the scientific literature led us to propose that, in conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…However, things might not be as simple as described above, since the biosynthesis of bioactive molecules is usually triggered by some specific physiological or environmental conditions, often linked to nutritional limitation and growth slowdown [12,35], and these molecules are believed to fulfill important regulatory roles for the producing bacteria in such contexts [12]. For instance, S. coelicolor, a strain characterized by an active oxidative metabolism consuming acetylCoA and thus bearing a low lipid content, produces antibiotics proposed to contribute to the regulation of its energetic metabolism [12]. Our data suggested that the existence of a negative correlation between lipid content and antibiotic activity, previously established for S. coelicolor, was also true for most Streptomyces strains, at least on R2YE glucose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, things might not be as simple as described above, since the biosynthesis of bioactive molecules is usually triggered by some specific physiological or environmental conditions, often linked to nutritional limitation and growth slowdown [12,35], and these molecules are believed to fulfill important regulatory roles for the producing bacteria in such contexts [12]. For instance, S. coelicolor, a strain characterized by an active oxidative metabolism consuming acetylCoA and thus bearing a low lipid content, produces antibiotics proposed to contribute to the regulation of its energetic metabolism [12]. Our data suggested that the existence of a negative correlation between lipid content and antibiotic activity, previously established for S. coelicolor, was also true for most Streptomyces strains, at least on R2YE glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of such antibiotics is thus expected to be reduced on glycerol. Antibiotics of this class (defined as class II in Virolle, 2020 [12]) are thought to have anti-oxidant functions via their ability to capture electrons from the respiratory chain to prevent the formation of ROS or NOS, but in doing so, they would also be inhibitory to respiration and thus toxic for living cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations